الصلابة النفسية وعلاقتها بالتحصيل المعرفي وبعض مهارات كرة الطائرة لطلاب التربية البدنية وعلوم الرياضية في جامعة كركوك - الحوري, عكلة سليمان; جرو, حميدة; الجبوري, احمد جاسم (Sulaimani Journal for Humanities, 2018)
The importance of the study is to stand on the level of psychological rigidity and cognitive achievement and some basic skills of students, and then identify the relationship between the degree of mental rigidity on the one hand and cognitive achievement and basic skills of volleyball, on the other hand to students of the Faculty of Physical Education at the University of Kirkuk. The aim of the research is to: مجلة )زانکۆی سلێمانی( القسم )B )للدراسات االنسانیة – العدد )65( عدد خاص لمؤتمر الدولي األول لكلیة التربیة الرياضية 575 • Identify the level of psychological rigidity and cognitive achievement and basic skills for students of the Faculty of Physical Education and Sports Sciences / Phase I. • To identify the relationship between psychological rigidity and cognitive achievement of students of the Faculty of Physical Education and Sports Sciences / the first stage. • To identify the relationship between psychological rigidity and basic skills of students of the Faculty of Physical Education and Sports Sciences / Phase I. The researchers hypothesized: • There is no significant relationship between psychological hardness and cognitive achievement of students of the Faculty of Physical Education and Sports Sciences / Phase I. • There is no significant relationship between the psychological hardness and basic skills of students of the Faculty of Physical Education and Sports Sciences / the first stage. The descriptive approach was used in the method of surveying and linking to its suitability and the nature of the study and its problem. The sample of the research was chosen in a deliberate manner and represented the students of the Faculty of Physical Education / the first phase of the academic year 2016-2017. The final sample of the sample was (50) students representing 20 86% of the total population of (58) students. The researchers used a selection of measures (psychological hardness and cognitive achievement) as well as tests of basic skills in volleyball (sentencing, scrolling, crushing beating). The researchers reached a number of conclusions, the most important of which are: • Positive relationship between psychological rigidity and cognitive achievement of students of physical education and sports sciences at the University of Kirkuk. • There is a significant relationship between psychological hardness and the basic skills of students of physical education and sports sciences.